Financing the growth of SMEs in Africa: What are the contraints to SME financing within ECOWAS? - Peter Quartey; Ebo Turkson; Joshua Yindenaba Abor; Abdul Malik Iddrisu (Review of Development Finance, 2017)
This study attempts to provide some understanding about SMEs' access to finance within the West African sub-region with particular interest in establishing whether there are similarities and/or differences in the determinants of SMEs access to finance across countries in SSA. For robustness sake, we developed both subjective and objective measures of access to finance. Using data from World Bank's Enterprise Survey data set, we examine the determinants of access to finance both at the sub-regional level and at the country-level. We found that, generally, at the sub-regional level, access to finance is strongly determined by factors such as firm size, ownership, strength of legal rights, and depth of credit information, firm's export orientation and the experience of the top manager. However, we found important differences in the correlates of firms' access to finance at the country level. The findings of this study therefore have important implications for policy.
Keywords: 650; Finance; SMEs; Growth; Constraints; ECOWAS; Africa